Equilibrium Pricing in the Scrap Car Market - Lim, Chin (Institutional Knowledge at Singapore Management University, 1991)
Traffic congestion is a critical and highly visible urban problem. In land scarce Singapore, the problem is even more crucial and the government has resorted to gargantuan measures not only to curb car use but also car ownership. Besides a plethora of road-use taxes, a unique tax structure on car ownership is employed that comprises hefty taxes on new car purchases plus provisions for tax discounts if new car purchases are accompanied by the scrappage of old cars. Consequently, a thriving scrap car market has evolved in which scrap car prices exceed even new car prices in some other countries. This paper constructs a theoretical model to explain the determination of the equilibrium scrap car prices. The equilibrium properties are subject to empirical tests. The paper also discusses the welfare implications of this unique policy scheme.